Mechanistic insights into an axon death pathway controlled by NAD-related metabolism - Loreto, Andrea (2018)
Studies of axon degeneration following an injury, known as Wallerian degeneration, and the axon-protective protein WLDs revealed a strong link between NAD metabolism and the mechanisms resulting in axonal destruction. Current knowledge indicates that the labile axonal NAD-synthesising enzyme NMNAT2 is essential for axonal survival. Its depletion, following an injury or its genetic removal, causes axon degeneration or defective axon growth. We recently proposed a key role for NAD-precursor NMN, which rapidly accumulates in transected nerves as a consequence of NMNAT2 depletion, in initiating axon degeneration after injury. Pharmacological and genetic reduction of NMN levels, by inhibition of NMN-synthesising enzyme NAMPT or expression of the bacterial NMN-scavenging enzyme NMN deamidase, robustly delays Wallerian degeneration. Recent evidence suggests that NMNAT2 and the pro- degenerative protein SARM1 cooperate in a core pathway regulating axon degeneration. It is important to fully understand the mechanism of Wallerian degeneration because related mechanisms could contribute to axon loss in several disease models, including peripheral neuropathies, Parkinson’s disease, multiple sclerosis and glaucoma. This thesis focuses on elucidating the mechanism by which NMN promotes axonal degeneration. I show that downstream events of NMN accumulation after injury include an increase in intra-axonal Ca2+ that immediately precedes axonal fragmentation. NMN requires the recently identified pro-degenerative protein SARM1 to promote Ca2+ rise and axon degeneration. Whilst these data suggest that mitochondrial dysfunction has no influence on the timing of axonal degeneration after injury, they also indicate that NMNAT2 depletion and NMN accumulation promote degeneration of uninjured axons exposed to the mitochondrial toxins CCCP and rotenone. These results identify critical steps of Wallerian degeneration where pharmacological intervention could be most successful. They also support the importance of NMNAT2 and NMN in controlling axonal health which goes beyond the simple regulation of Wallerian degeneration and potentially into mitochondrial disorders, including Parkinson’s disease, Friedreich's ataxia and multiple sclerosis.